Zirconium carbide (ZrC) synthesised via chemical vapour deposition (CVD) and spark plasma sintering (SPS) and phase formation of iridium (Ir) films deposited on ZrC at relatively low temperatures - Malherbe, Johan B. (University of Pretoria, 2020)
Thesis (PhD (Physics))--University of Pretoria, 2019.